Laminin‐221 Enhances Therapeutic Effects of Human‐Induced Pluripotent Stem Cell–Derived 3‐Dimensional Engineered Cardiac Tissue Transplantation in a Rat Ischemic Cardiomyopathy Model. Issue 16 (18th August 2020) - Samura, Takaaki; Miyagawa, Shigeru; Kawamura, Takuji; Fukushima, Satsuki; Yokoyama, Jun‐ya; Takeda, Maki; Harada, Akima; Ohashi, Fumiya; Sato‐Nishiuchi, Ryoko; Toyofuku, Toshihiko; Toda, Koichi; Sekiguchi, Kiyotoshi; et al.
Abstract : Background: Extracellular matrix, especially laminin‐221, may play crucial roles in viability and survival of human‐induced pluripotent stem cell‐derived cardiomyocytes (hiPS‐CMs) after in vivo transplant. Then, we hypothesized laminin‐221 may have an adjuvant effect on therapeutic efficacy by enhancing cell viability and survival after transplantation of 3‐dimensional engineered cardiac tissue (ECT) to a rat model of myocardial infarction. Methods and Results: In vitro study indicates the impacts of laminin‐221 on hiPS‐CMs were analyzed on the basis of mechanical function, mitochondrial function, and tolerance to hypoxia. We constructed 3‐dimensional ECT containing hiPS‐CMs and fibrin gel conjugated with laminin‐221. Heart function and in vivo behavior were assessed after engraftment of 3‐dimensional ECT (laminin‐conjugated ECT, n=10; ECT, n=10; control, n=10) in a rat model of myocardial infarction. In vitro assessment indicated that laminin‐221 improves systolic velocity, diastolic velocity, and maximum capacity of oxidative metabolism of hiPS‐CMs. Cell viability and lactate dehydrogenase production revealed that laminin‐221 improved tolerance to hypoxia. Furthermore, analysis of mRNA expression revealed that antiapoptotic genes were upregulated in the laminin group under hypoxic conditions. Left ventricular ejection fraction of the laminin‐conjugated ECT group was significantly better than that of other groups 4 weeks after transplantation. Laminin‐conjugated ECT transplantation was associated with significant improvements in expression levels of rat vascular endothelial growth factor. In early assessments, cell survival was also improved in laminin‐conjugated ECTs compared with ECT transplantation without laminin‐221. Conclusions: In vitro laminin‐221 enhanced mechanical and metabolic function of hiPS‐CMs and improved the therapeutic impact of 3‐dimensional ECT in a rat ischemic cardiomyopathy model. These findings suggest that adjuvant laminin‐221 may provide a clinical benefit to hiPS‐CM constructs.